Healthcare Quality under Performance Based Financing in Cameroon: Lessons Learned and Perspectives - Ngehdzeka, Chin Erick; Njoumemi, Zakariaou; Takougang, Innocent (British Journal of Healthcare and Medical Research, 2025)
Healthcare quality remains one of the primary policy concerns towards achieving universal health coverage (UHC) that shapes health sector reform in low- and middle-income countries (LMICs). In this perspective, performance-based financing (PBF) is an innovative well-structured health system financing mechanisms which aims to improve coverage and healthcare quality by incentivizing providers and facilities to achieve specific performance targets, often including quality indicators. During the last fifteen years, Cameroon used the PBF as a key health financing policy while in 2023 the policymakers engaged the implementation of UHC as part of the country effort to improve coverage and access to quality health services nationwide. This paper aims to analyze the healthcare quality under the Performance-Based Financing (PBF) mechanisms’ intervention in Cameroon. A qualitative cross-sectional design was undertaken using a scoping review methods for data collection and analysis. The results point out that PBF mechanisms use bonuses or other incentives, which may include equipment or individual staff payments, based on the achievement of some outcome’s targets. By linking performance measurement to incentives, PBF helps address quality shortfalls and encourage providers to improve their efficiency and responsiveness to population needs. Incentivizing quality encourage providers to improve healthcare quality by linking bonuses or other incentives to the achievement of specific quality indicators. Focusing on specific areas of healthcare quality improvement, such as maternal and child health or HIV/AIDS care or immunization, nutrition, sanitation, functional infrastructure, medical supplies’ availability, hiring qualified health workers, etc. enhanced the overall performance. Improved staff motivation by providing incentives thereby improving process healthcare quality. Increased facility quality by investing bonuses to improve structural aspects can enhance the healthcare quality. PBF’s payments depend explicitly on the degree to which services are of approved healthcare quality, as specified by protocols for processes or outcomes. However, healthcare quality measurement can be challenging, and PBF mechanisms need to develop effective and relevant quality indicators. The effectiveness of PBF mechanisms for improving healthcare quality can vary depending on the context in which they are implemented. Therefore, overall, PBF is a potentially effective tool for improving healthcare quality, but it's essential to consider the challenges and adapt PBF mechanisms to specific contexts and population needs. These results highlight how crucial it is to improve performance metrics, boost domestic funding for UHC, and fortify legislative frameworks in order to guarantee long-lasting gains in healthcare quality. This analysis contributes to broader debates on performance-based financing and health system reform in low- and middle-income countries.